FAKTOR – FAKTOR PENGARUH EFEKTIVITAS KEBIJAKAN SEKOLAH Studi Kasus SMK PGRI Klungkung - A. A Ngr. A. Wira Bima Wikrama; Ni Ketut Ari Utami (Jurnal Ilmiah Cakrawarti, 2021)
The world of formal education is one of the factors in producing quality human resources (HR), and is an absolute requirement for creating quality work and results. Many factors influence the educational process. One of the most decisive is school policy. School policy will greatly depend on the role of a teacher as an educator in carrying out educational activities and supervision of the school policy system to produce good and quality educational performance. Teachers who are qualified and show effective performance will greatly affect the performance of education itself. This is also what should apply and run at SMK PGRI Klungkung.This study focuses on the Factors Influencing the Effectiveness of School Policies. The research method was carried out with qualitative descriptions combined with quantitative and data analysis using descriptive narratives, namely data reduction, data presentation and triangulation.The results of the study indicate that there are eight factors that influence the effectiveness of school policies. Therefore, the effectiveness of school policies in improving educational performance at SMK PGRI Klungkung has a very good category in terms of planning, management, reporting and evaluation systems.